Estimation of Curie point depths in the Southern Vietnam continental shelf using magnetic data - Luan, Pham Thanh; Thanh, Do Duc; Oksum, Erdinc; Sang, Le Thi (Vietnam Journal of Earth Sciences, 2019)
This study attempts to estimate the thermal structure in the Southern Vietnam continental shelf by calculating the Curie point depth isotherm using magnetic data. The Curie point depth values, from 49 overlapping blocks 128 × 128 km in size, have been estimated by the exponential approach. This approach is based on the analytical solution of the exponential equations obtained from transforming the magnetic anomaly data into the frequency domain. According to the obtained results, the range of Curie point depths is from 15.3 to 35.6 km. In the study area, the greatest Curie point depth is located in the South-Eastern part, and the smallest depth is located at North-Western part. The heat flows derived from the Curie point depths are also presented. The obtained results are at relatively high resolutions and in agreement with the published information available for the study area. The Curie point depths generally lie below the Moho surface in this region but lie above in some locations, notably the Cuu Long basin.